2008
DOI: 10.1021/ef800270x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Low-Frequency Alternative Flame Behaviors in a Lean Premixed Combustor

Abstract: Combustion instability causes severe problems, such as fatal damage to lean premixed gas turbine combustors and shortening the lifetime of the overall system. In this study, to understand the instability phenomena, an experimental study and a numerical simulation were conducted in a dump combustor with respect to the modulation of the fuel flow, that is, the choked fuel flow and the unchoked fuel flow. The fluctuations of pressure and heat release were measured by a piezoelectric pressure sensor and high-speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…However, the intermittency that we refer to involves bursts of high-amplitude periodic oscillations from a background of low-amplitude chaotic or aperiodic fluctuations. This type of intermittency is comparable to the observations of sporadic 'noisy' and 'quiet' states reported in Hong et al (2008) and Arndt et al (2010).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the intermittency that we refer to involves bursts of high-amplitude periodic oscillations from a background of low-amplitude chaotic or aperiodic fluctuations. This type of intermittency is comparable to the observations of sporadic 'noisy' and 'quiet' states reported in Hong et al (2008) and Arndt et al (2010).…”
Section: Introductionsupporting
confidence: 90%
“…Hong et al (2008) studied the effect of pressure fluctuations on fuel flow modulations in a swirl combustor. They reported the presence of pressure oscillations with an alternate 'noisy period of 200 Hz fluctuation and a silent period with a small pressure fluctuation' for an unchoked fuel flow at the injector (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For an unchoked fuel flow at the injector in a swirl combustor, Hong et al (2008) reported the presence of pressure oscillations that alternated between a 'noisy period of 200 Hz fluctuation and a silent period with a small pressure fluctuation'. Arndt et al (2010) have observed a transition in the flame dynamics between a state of stable combustion and self-excited oscillations in a premixed gas turbine model 472 V. Nair, G. Thampi and R. I. Sujith combustor using simultaneous OH * chemiluminescence, OH * planar laser-induced fluorescence (PLIF) and stereoscopic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-periodic and chaotic oscillation: Quasi-periodic pulses about every 0.1 s have been observed by Hong et al 135 in a dump combustor and shown to be associated with equivalence ratio fluctuations and the lifting of the premixed flame in a regime of mean equivalence ratio approaching that of lean blow-out. Also in that regime, Nair et al, 136 Domen et al 137 and Unni and Sujith 138 examine intermittency in pressure fluctuations on a similar timescale in a swirled combustor and proposed it as a diagnostic for blow-out.…”
Section: Non-linear Observations In Flamesmentioning
confidence: 93%